IMPLEMENTASI PROGRAM PEKARANGAN PANGAN LESTARI (P2L) PADA MASYARAKAT DESA SUMBERDUREN KECAMATAN KRUCIL KABUPATEN PROBOLINGGO - Sucahyo, Imam; Rahmandi, Andhi Nur; Firguntoro, Tofan (Universitas Panca Marga, 2025)
Abstract Population growth increases food needs and shrinks land. Based on Law 18/2012 and Government Regulation 17/2015, food diversity is attempted to be increased through Pekarangan Pangan Lestari (P2L), targeted the use of unproductive yard land as a producer of nutritious and market-oriented food. The implementation in Probolinggo Regency is in Krucil District. Obstacles were found; 1) lack of human resources, 2) low understanding, 3) low vegetable consumption. In the public policy implementation realm, this is related to the implementation gap and implementation capacity which is interesting to research using a descriptive-qualitative approach. Data gathering is carried out through interviews, observation and documentation, coupled with Interactive Model analysis. The result of the P2L Program implementation in Krucil District is located in Sumberduren Village through Farmers Group Makmur 01. In terms of implementation based on Meter and Horn, the communication aspect went well, with several obstacles. The qualification of implementers is also adequate, but lack in terms of numbers. Other resources is adequate, as for the funds is amount to 15 million/each farmer group are deemed insufficient. The disposition of implementers and policy targets show an attitude of support, especially for members of Poktan Makmur 01 as policy beneficieris. Keywords: Public policy implementation, P2L Program, P2L Krucil District.